Sistem Otomatis Pengendalian Pakan Ikan dengan Sumber Energi Matahari Menggunakan Mikrokontroller Arduino - Atika, Ratna; Yusya Whardani, Dyah Utari (Jurnal Ampere, 2023)
Humans have made many discoveries in the modern era that make work easier, including advances in technology, healthcare, agriculture, and cultivation. Automated methods and equipment are among thedevelopments that make human work easier. As a result, a device for feeding fish that can functionautomatically according to the feeding plan and time is designed using a servo motor controller for the fishfeeder powered by solar energy and an Arduino microcontroller module as the controller program. Solarpanels are power plants that receive power from sunlight and are equipped with a charge controller. Theinverter acts as a DC to AC voltage converter, while the battery stores and distributes the voltage. Thescheduling system used by this tool is determined by Arduino software that has been programmed in astructured manner. It will operate on a pre-set schedule, which requires it to be used between 8 am and 5pm, and its output capacity of 10 feed container valve openings is set consistently and pre-programmed.During the test, the average power consumption was 142.75 watts during the day and 125.72 watts at night,with a total consumption of 108.93 watts at night.